Manajemen Organisasi Forum Pemuda Lintas Agama dalam Menjaga Kerukunan antar Umat Beragama di Kota Tomohon - Tulung, Jeane Marie; Ering, Aljuanika Ertamaya; Waney, Mercy W. K. (Jurnal Manajemen Pendidikan Kristen, 2023)
Interfaith youth forum has a positive impact in maintaining and maintaining harmony among religious communities. This study aims to describe how the interfaith youth forum management in maintaining harmony between religious communities in the city of Tomohon, describes the causes of pelita forum management in maintaining harmony between religious communities in the city of Tomohon, describing the efforts of interfaith youth forum management in maintaining inter-religious harmony in the city of Tomohon. Observations and interviews were carried out on interfaith youth forum participants to obtain data in this study. After the data is collected the data is analyzed. The management of the interfaith youth forum in maintaining harmony among religious communities in the city of Tomohon is as a means of communication between youth across religions, as a forum for accommodating aspirations, and a provision to be a buffer in religious problems that occur. The inhibition of interfaith youth forum management in maintaining harmony among religions in the city of Tomohon is caused by the attendance of participants who were late when the forum activities were carried out, busyness or fatigue that resulted in not attending the forum activities, and the presence presence that was represented by Christianity, Catholicism and Islam. While the efforts of interfaith youth forum management in maintaining harmony among religious communities in the city of Tomohon are by carrying out activities that are supported by adequate facilities, inviting youth organization leaders, and presenting religious leaders in the implementation of the interfaith youth forum activities. To that end, the interfaith youth forum must continue to be carried out to maintain tolerance and harmony between religious communities